O coordenador pedagógico e a formação continuada de professores em serviço : uma análise em escolas públicas da região metropolitana do estado de Sergipe - Sampaio, Mariana Muniz (2018)
The path taken along this research had the objective of analyzing the relationship of the Pedagogical Coordinator with the Continued Training of Teachers in Service in the State Public Schools of Sergipe. With the backing of the line of thought of renowned authors such as Bernard Charlot and Maria Amélia do Rosário Santoro Franco, we chose our direction, and to build our conception of Ongoing Teacher Training, we have taken steps in the theories of Imbernón (2010), Tardif 2002, 2007) and Perrenoud (2001, 2002). As this conception of Continuing Formation brings in itself a specific Pedagogical Coordinator profile, we walk side by side with the ideas of Almeida and Placco (2005) and Domingues (2014). We also have documentary sources for the theoretical reference of this work. As a qualitative study, based on a survey conducted with schools in the capital and the region of Greater Aracaju, we conducted a documentary analysis and a semi-structured interview with ten Pedagogical Coordinators, selected by schools with a larger number of students in the year of 2016 In some moments, we can also observe formations promoted by the SEF - Service of Elementary Education, sector that is part of the DED - Department of Education, SEED - Secretary of State for Education. These observations were from the formative meetings with a much larger audience, and in several regional directorates of the State. For data analysis, we use Bardin's theory (2008), considering the statements of the Pedagogical Coordinator what their perceptions and knowledge about the Continued Training of Teachers in Service. What we can see from what has been covered is that the Pedagogical Coordinators of schools in the State of Sergipe have a conflictive relationship with the Continuing Education of Teachers in Service, since they can not develop a trainer profile due to the demands of the other assignments and to the functional structure of the Magisterium in the State. However, positively, the data show that these coordinators wish to develop this training profile and recognize the need for continuous training that promotes the professional development of teachers